Knowledge on recycling among Orang Asli primary school children in Sekolah Kebangsaan Penderas, Kuala Krau, Pahang - Abdul Rahman, Haliza; Mohd Sham, Shaharuddin (Human Resource Management Academic Research Society, 2020)
Introduction: Recycling activities are the process of collecting, sorting and reprocessing certain materials which considered as waste into a new product. Objective: The aim of this study was to assess the knowledge of the Orang Asli school children before and after the running of a promotional and educational program on recycling through questionnaires. Method: A questionnaire-based study was conducted to assess the knowledge of the Orang Asli school children on recycling. Result: Overall, respondents have had some knowledge about recycling before joining this program. An increase in knowledge were evident after they sat for the program. Most of them acquired the knowledge through mass media. Broadcast media were important avenues to obtain information on recycling. Respondents were more knowledgeable to recycle items that were visually available to them. Conclusion: Parents, school authorities and society at large has the responsibility to educate children at the earliest possible age on the importance of recycling.